ANALISIS HEGEMONI DALAM DWILOGI NOVEL NEGERI PARA BEDEBAH KARYA TERE LIYE (PERSPEKTIF ANTONIO GRAMSCI) - Ida Nuswantaria (EDU-KATA, 2019)
This research aimed ad describing (1) the types of hegemony that included physical and psychological hegemony. (2) the techniques of hegemony, including oppressive, intellectual, and moral hegemony. (3) thescopeof hegemony, including micro and macro. Thisresearch used Gramsci Antonio Theory.This research uses qualitative method. The sources of data are novels by TereLiye entitled Negeri Para Bedebah and Negeri Diujung Tanduk novels. Data collection used documentation, reading, and taking note. Data were analyzed descriptively. Validity of data was tested by using close observation and triangulation.The results of the research are as follows: (1) the types of hegemony in the two novels are physical hegemony and psychology hegemony. (a) physical hegemony includes the hegemony of the police to thomas, Wusdi to Thomas, SAR the Hongkong Antiteror Force to Kadek, SAR to Opa, Thomas, and Maryam. (b)psychology hegemony includes the General Commisioner police officer to Thomas, Opa to Thomas, Julia to Thomas , Thomas to Maggie, Thomas to Julia and Ram to Opa. (2) hegemony techniques used are oppressive,intellectual, and morality hegemony. Oppressive method are being practiced by Mr. shinpei at Thomas’ family using his minions; wusdi, Tunga and Ram. Intellectual and morality hegemony are divided into three: (1) traditional intellectual included (a) Thomas to Maggie and (b) JD to Thomas, (2) organic intellectual included (a) Maryam to Thomas, (b) Detective Liu to Thomas, and (3) Thomas to JD, and (3) consensus includes (a) Thomas to Lee, (b) Maryam to Thomas , (c) Thomas to jailer officer, and (d) Thomas to client. (3) Hegemony scope includes (a) micro hegemony includes Liem to Edward and Mama to Thomas, and (b) macro hegemony includes wusdi to Thomas , Ram to Tunga and wusdi and JD to Thomas. Hegemonies in thi scope are also done in the economic and political perspectives.